What's in a Name? Implicit Bias Affects Patient Perception of Surgeon Skill. Issue 6 (25th May 2021) - Bhat, Deepa; Kollu, Tejas; Ricci, Joseph A.; Patel, Ashit
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Implicit bias is the unconscious associations and beliefs held toward specific demographic groups. Instagram is commonly used by plastic surgeons to market their practice. This study investigates whether a surgeon's name on a social media platform influences perception of their competence and their likelihood of gaining a new patient. Methods: A mock Instagram post was created using before-and-after photographs of a breast augmentation patient. Eight different ethnicities were selected, and common female and male names were selected based on U.S. Census data for each ethnicity. Surveys using the Instagram post were distributed asking responders to evaluate the competency of the surgeon and how likely they are to become a patient of that plastic surgeon. The surgeon's name was the only variable in the survey. Results: A total of 2965 survey responses were analyzed. The majority of responders were Caucasian (57 percent); 55 percent were men and 45 percent were women. Overall, competence and recruitment likelihood scores between surgeons of different ethnicities were not significantly different. Caucasian and Latinx responders both assigned higher competence and recruitment likelihood scores to their own respective ethnicities. Conclusions: Implicit bias plays a role in whether or not a patient is likely to seek care from a surgeon with an ethnically identifiable name. The two most common cosmetic surgery demographic groups, Caucasians and Latinxs, were also the only two ethnic groups to display in-group favoritism. Public education should be directed toward surgeon qualifications and experience in an effort to reduce implicit bias on patient decision-making.